1998
DOI: 10.1001/archinte.158.14.1543
|View full text |Cite
|
Sign up to set email alerts
|

A Hospital-Based Pharmacy Intervention Program for Pneumococcal Vaccination

Abstract: A hospital-based pharmacy vaccination program that relied on simple chart reminders was significantly associated with increased vaccination rates among inpatients at risk for invasive pneumococcal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…A study of 102 patients reported an increase in pneumococcal and influenza vaccination rates from 21% and 16% to 67% and 61%, respectively ( P = 0.0001) . Specifically, for pneumococcal vaccine chart reminders, Vondracek et al reported an increase in vaccination rates in 80 patients from 0% to 28.8% and Skledar et al reported an increase in vaccination rates in 1967 patients from 1% to 32.5% . Our study has demonstrated a similar increase in vaccination rates with the involvement of a pharmacist; however, it adds an understanding of the economic advantage of utilizing a pharmacy resident from the hospital perspective.…”
Section: Discussionsupporting
confidence: 55%
“…A study of 102 patients reported an increase in pneumococcal and influenza vaccination rates from 21% and 16% to 67% and 61%, respectively ( P = 0.0001) . Specifically, for pneumococcal vaccine chart reminders, Vondracek et al reported an increase in vaccination rates in 80 patients from 0% to 28.8% and Skledar et al reported an increase in vaccination rates in 1967 patients from 1% to 32.5% . Our study has demonstrated a similar increase in vaccination rates with the involvement of a pharmacist; however, it adds an understanding of the economic advantage of utilizing a pharmacy resident from the hospital perspective.…”
Section: Discussionsupporting
confidence: 55%
“…According to the surveys by the US Centers for Disease Control and Prevention, approximately 20% of persons aged ≥65 years who said they received influenza vaccines reported never having received a pneumococcal vaccination, indicating missed opportunities for pneumococcal vaccine administration at the time of influenza vaccination 10,11. Previously, many in-hospital campaigns have focused on the pneumococcal vaccination of high risk inpatients prior to discharge using computerized reminders, standing order programs, or pre-printed order programs 12,13. Although such strategies might be effective in improving pneumococcal vaccine coverage, a more diverse approach is needed to cover the large population of high risk individuals who are not hospitalized.…”
Section: Discussionmentioning
confidence: 99%
“…Because nearly one out of 288 288 288 288 288 three of the patients with invasive pneumococcal disease admitted to Hospital A during 1994 to 1997 had been hospitalized there in the previous 6 months, an inpatient screening and vaccination program could have prevented a substantial number of cases. Hospital-based programs have been shown to be effective in vaccinating highrisk adults in other settings (19)(20)(21), and the use of standing orders to vaccinate eligible adults with pneumococcal vaccine has been recommended by the Task Force on Community Preventive Services (22). Adult vaccination programs in nontraditional settings (e.g., pharmacies, churches, and the workplace) might further raise vaccination coverage in this area (23).…”
Section: Discussionmentioning
confidence: 99%